Analysis of live interactive teledermatologic consultations for prisoners in Korea for 3 years. (October 2018) - Seol, Jung Eun; Park, So Hee; Kim, Hyojin
Introduction: Teledermatology has contributed to the enhanced accessibility of underserved populations. This study investigated the prevalence and clinical outcomes of dermatologic diseases in prisoners in Korea through live interactive teledermatology (LITD) Method: The medical records of patients in a Busan prison, who interacted with a dermatologist using LITD from July 2013 to August 2016, were reviewed retrospectively. Results: The mean age of the 406 patients enrolled in the study was 39.0 years and 91.4% were male. Infectious disease (42.8%) was the most common type of disease, followed by eczematous disease (29.4%) and diseases of the skin appendages (14.5%). Among the 187 (38.2%) patients who had a follow-up consultation, 162 (86.7%) showed clinical improvement, whereas 21 showed either no change or a worse clinical outcome. Twenty patients were diagnosed with different types of dermatologic disease at follow-up consultations. Discussion: LITD can contribute to a favourable clinical outcome and may thus be an effective alternative to face-to-face consultation in prisoners and other underserved populations.